2003
DOI: 10.1083/jcb.200304128
|View full text |Cite
|
Sign up to set email alerts
|

Smn, the spinal muscular atrophy–determining gene product, modulates axon growth and localization of β-actin mRNA in growth cones of motoneurons

Abstract: Spinal muscular atrophy (SMA), a common autosomal recessive form of motoneuron disease in infants and young adults, is caused by mutations in the survival motoneuron 1 (SMN1) gene. The corresponding gene product is part of a multiprotein complex involved in the assembly of spliceosomal small nuclear ribonucleoprotein complexes. It is still not understood why reduced levels of the ubiquitously expressed SMN protein specifically cause motoneuron degeneration. Here, we show that motoneurons isolated from an SMA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
578
1
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(618 citation statements)
references
References 50 publications
30
578
1
4
Order By: Relevance
“…Thus, SMN deficiency did not seem to interfere with iPSC differentiation but severely restricted neurite outgrowth. This phenotype is similar to the deficit exhibited by cultured SMA motoneurons isolated from mice or patients [14,25]. Restoration of neurite outgrowth by SMN expression suggested that this deficit was indeed caused by SMN deficiency and not by iPSC clonal variation.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, SMN deficiency did not seem to interfere with iPSC differentiation but severely restricted neurite outgrowth. This phenotype is similar to the deficit exhibited by cultured SMA motoneurons isolated from mice or patients [14,25]. Restoration of neurite outgrowth by SMN expression suggested that this deficit was indeed caused by SMN deficiency and not by iPSC clonal variation.…”
Section: Resultssupporting
confidence: 69%
“…However, SMN deficiency causes profound effects only on motoneurons but not on other cell types. SMN also exists in the axonal compartment of motoneurons where it is associated with heterogeneous nuclear RNP R and interacts with the 3 0 untranslated region of b-actin mRNA [11][12][13][14]. Reduced SMN results in lower levels of b-actin mRNA and protein in axons and growth cones.…”
Section: Introductionmentioning
confidence: 99%
“…L'une des dernières observations réalisées concerne une maladie génétique neuromusculaire très fréquente chez l'homme, la SMA (spinal muscular atrophy, amyotrophie spinale), qui pourrait trouver son origine dans un défaut de transport de cet ARNm [36]. Il ne fait nul doute que l'avenir réserve encore de belles découvertes.…”
Section: Discussionunclassified
“…In motor neurons, SMN is localized in growth cones, along the axon and in the pre-and post-synaptic sides of the neuromuscular junctions (NMJs) [Francis et al, 1998;Broccolini et al, 1999; La Bella et al, 2000;Pagliardini et al, 2000;Fan and Rossoll et al, 2002] where it forms a macromolecular complex distinct from the nuclear SMN complex [Zhang et al, 2006]. The SMN protein is subject to cytoskeletal-based, bidirectional transport between the soma and growth cones suggesting that SMN may have a cytoplasmic function related to neuronal transport of proteins and mRNA required at the distal tips of axons [Zhang et al, 2003;Rossoll et al, 2003; Jablonka et al, 2004;Fallini et al, 2012]. Hints regarding neuronal-and muscle-specific SMN functions were recognized through the identification of interacting proteins in the SMN-complex.…”
Section: Smn: How Many Functions Can a Single Protein Possess?mentioning
confidence: 99%